Pelatihan Pembuatan Pupuk Organik Cair Bagi Siswa SMA IT Al Fatih Makassar Untuk Mendukung Pertanian Berkelanjutan - Wiharto, Muhammad; Lodang, Hamka; Junda, Muhammad; Amboupe, Dewi Sartika; Ayu Anggita, Sri (Education and Talent Development Center Indonesia, 2025)
Abstract Socialization and training activities on liquid organic fertilizer (POC) production for high school students in urban areas were carried out with the aim of increasing the knowledge and skills of urban students in managing organic waste into products that are economically valuable and environmentally friendly. Household waste, especially food scraps and other organic waste, has great potential to be processed into POC that can be used as an alternative fertilizer for plants. This activity involved the active participation of students, focusing on providing information about the benefits of POC, simple and easy-to-apply production techniques, and hands-on practice in making POC using readily available materials. The results of this activity showed an increase in participants' understanding of the importance of organic waste management and the potential of POC as a sustainable fertilizer solution. In addition, participants were able to practice making POC independently, which is expected to reduce the volume of waste disposed of in landfills and increase soil fertility and crop productivity in the surrounding environment. Thus, this outreach and training activity made a positive contribution to creating a clean, healthy, and productive environment through the optimal utilization of household waste in urban areas.